Improving Employee Performance through Green Human Resource Management Practices - Intan Ratna Wati; Aulia Vidya Almadana (Universitas Muhammadiyah Yogyakarta, 2025)
This study investigates the impact of green human resource management (HRM) practices on employee performance within the state banking sector, emphasizing the mediating roles of transformational leadership, employee affective commitment, and readiness to change capability. A quantitative research design was employed, utilizing purposive sampling to select participants. Data were gathered through online and in-person questionnaires, with follow-up reminders increasing the response rate. A total of 500 questionnaires were distributed, yielding 390 responses, with 360 deemed valid and subsequently included in the analysis. Structural equation modeling (SEM) and multivariate analysis were used to test the hypotheses and examine relationships between variables. The findings confirmed that green HRM practices enhanced employee performance by fostering affective commitment and change readiness. Transformational leadership further strengthens this relationship by improving employees’ adaptability and engagement. This study’s novelty lies in integrating green HRM with transformational leadership and change readiness as key mechanisms for improving employee performance. However, its focus on affective commitment limits the generalizability of findings, as other forms of commitment remain unexplored. Additionally, combining private and state-owned bank respondents may obscure sector-specific insights. Future research should address these gaps by expanding the scope to different industries and assessing practical applications of green HRM strategies.